Community Empowerment Based on Muhammadiyah Mosque in Maros-Pangkep, South Sulawesi - Suarni, Agusdiwana; Busri, Andi Zulfikar; Wahyuni, Sri; Nugroho, Dimas Adi (Universitas Muhammadiyah Makassar, 2025)
This study explores the strategic role of Muhammadiyah mosques as centers for community empowerment in the districts of Maros and Pangkep, South Sulawesi, Indonesia. Utilizing a qualitative research design, data were gathered through in-depth interviews with 12 mosque administrators across selected Muhammadiyah mosques. The findings demonstrate that these mosques serve beyond their religious function, acting as hubs for socio-economic and educational development. Various empowerment initiatives ranging from entrepreneurship training, zakat and waqf-based programs, to informal education highlight the mosque’s expanded role in improving community welfare. Despite these positive impacts, the study identifies key challenges, including limited public engagement, inadequate institutional capacity, and a lack of understanding regarding the mosque’s potential as a driver for sustainable development. The research underscores the importance of structured management strategies and leadership training to enhance mosque-based empowerment programs. Furthermore, it emphasizes the integration of Islamic social finance instruments and participatory governance as critical enablers. The results contribute to the broader discourse on faith-based community development and provide a practical framework for policymakers, religious leaders, and NGOs aiming to optimize mosque roles in societal transformation, particularly within the Muhammadiyah movement. This study affirms that mosques, when professionally managed, can function as powerful agents for inclusive and sustainable development.